Relationship Between Annual Rainfall Oscillations and Mohair Production in Lesotho Between 1935 and 1996 - Ng'ambi, J.W.; Norris, D.; Mbajiorgu, C.A. (Pakistan Journal of Nutrition, 2009)
This study was conducted to determine trends in annual rainfall oscillations and mohair production in Lesotho between 1935 and 1996. An exponential regression equation of the form LnY = LnA + bx was used to estimate trends. Between 1935 and 1965 Angora goat numbers, mohair production and mohair yield per goat increased (p0.05) at around one million animals. Mohair yield per goat declined (p